Analysis of user experience with TikTok Shop features among Generation Z in Balikpapan - Safitri, Sanrina Aprilia; Ar Rifana, Nabila Auliya; Servanda, Yustian; Fatma, Febrina (Yayasan Kita Menulis, 2026)
This study was conducted to determine the usability level of TikTok Shop features among Generation Z in Balikpapan. The main focus of this study was how easy these features were to use for the user experience when shopping on the TikTok Shop application. The method used was a quantitative approach using the System Usability Scale (SUS) instrument. Data was collected by distributing questionnaires to 27 respondents who were Generation Z aged 13 to 28 years old residing in Balikpapan. The SUS questionnaire consisted of 10 questions using a Likert scale of 1 to 5, which were then processed to obtain a usability score. The results of data processing showed that the total SUS score obtained was 2,230 with an average value of 82.59. This value indicates that the TikTok Shop feature has a high level of usability. In general, respondents felt that the interface was easy to understand, supported shopping activities, and was in line with Generation Z's social media usage habits. Based on these results, the researcher concluded that the TikTok Shop feature was well-designed and provided a positive experience for Generation Z in Balikpapan.